XAFS study of dried and reduced PtSn/C catalysts: nature and structure of the catalytically active phase - Román Martínez, M. C. (2000)
Bimetallic PtSn/C catalysts, prepared on two activated carbon supports of different surface chemistry by two different preparation procedures, have been analyzed by XAFS spectroscopy. The main goal is to identify the effect of the support surface oxidation and the preparation procedure (coimpregnation or successive impregnations) in the interaction of platinum with the support and/or with tin atoms. XAFS results reveal the effect of the mentioned variables in the structure of the supported phase. It has been found in dried samples that the interaction of the platinum species with the support is stronger if the carbon surface is oxidized. The two-step impregnation, compared with the coimpregnation method, renders samples with a stronger platinum-support interaction. Such an interaction determines the distribution of the active phase on the support particles. The structure of the metallic phase after reduction is quite different for samples prepared with the oxidized and nonoxidized carbon support and is also dependent on the preparation procedure. From the XAFS data, the presence of the following platinum containing structures is suggested: PtSn alloy, Pt-O-Sn2+ species and pure Pt clusters. The relative proportion of these structures in the catalysts and their distribution on the support determine the catalytic activity for cyclohexane dehydrogenation.